Minimasi Jarak Pengiriman Roti Cv. Twin Setia dengan Metode K-Means Clustering dan Simulated Annealing - Lukman Adhitama; Suci Murniati; Cahyono Sigit Pramudyo (Fakultas Teknik Universitas Pasifik Morotai, 2023)
The distribution process plays an important role in the industrial world because it regulates goods so that they reach consumers quickly. In order for this to be achieved, distribution needs to cover the minimum distance possible. In this research, optimization of the goods delivery route that CV Twin Setia's distribution vehicles need to pass through to deliver the bread products it sells to customers in Bantul Regency, Sleman Regency and Yogyakarta City. By using the k-means clustering method, customers are grouped into three clusters so that total demand does not exceed the vehicle's carrying capacity. Each cluster then determines the distribution route using the simulated annealing method by applying five parameter combinations. The final results show that the best distribution route obtained has a total distance of 212.7 km. These results are very optimal when compared to the initial route because there has been a reduction in distance of 125.1 km or 37.03%.